(3eMGSf GdCOH hGLJfGH GdQjHs - (3ehSi Hf jhSa Hf YjSi GdeGOQjfjs ((3Ydj Hf eMeO GdedbH H```` hdj s)
(3ChdgG (B:s
(3hHYO, abO GSJNQJ Gddg JYGdi aj LeY cJGH jfaY GdUZjQ hGdcHjQ hChdi GdQJH ef GdCYLGe hGdCJQGc hGdYQH hSejJg eMGSf GdCOH hGLJfGH GdQjH s
(3BNQgG (B:s
(3adh cGf GdEfSGf ojHUQ faSg dCZfGg Yf YjH GdUOjb hbUQG agPH faSc CjgG GdYGbd HEfcGQc Ydi YjhHc JYdjb eMGSf GdCOH hGLJfGH GdQjH s
(3HgG fXGe GdJYbjHIs
(3HBNQgG geRjI GHf GdYWGQ hHYV fbhd GOHjI aj fMh (B14 (3hQbIs
(3hgfGc Tc aj fSHI GdeNWhWI ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs